Relative Prices, Inflation and Core Inflation - Roger, Scott (IMF Working Papers; Working Paper ;, 2000)
Empirical evidence on the distribution of relative price changes almost invariably reveals high kurtosis and a tendency toward right-skewness. Simple mixed distribution models including volatile and infrequently adjusted prices can account for these and other common features, such as correlation between the mean and variance of relative prices. In such circumstances, robust measures of central tendency are likely to outperform the mean or standard measures of 'core' inflation as indicators of generalized inflation. The analysis also supports the use of geometric averaging in CPI construction and the targeting of the geometric mean inflation rate rather than the Laspeyres mean.